2004
DOI: 10.1177/0091270004267593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on the Number and Activity of Circulating Endothelial Progenitor Cells

Abstract: Recently, some studies have shown that nicotine increased neovascularization, which involves endothelial progenitor cells (EPCs). The effects of nicotine on EPCs are still unclear at present. Therefore, the authors investigated whether nicotine had influences on EPC number and activity. The EPCs were stimulated with nicotine (to make a series of final concentrations: 10(-12) mol/L, 10(-10) mol/L, 10(-8) mol/L, 10(-6) mol/L, 10(-4) mol/L) or vehicle control for the respective time points(12, 18, 24, 32, and 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 36 publications
3
47
0
3
Order By: Relevance
“…59 Smoking has been identified as an important risk factor for reduced EPC numbers in one of the first studies on cardiovascular risk factors by Vasa et al 46 However, Wang et al recently demonstrated that the role of nicotine is more complex than initially expected. 60 In an experimental study, they demonstrated that low concentrations of nicotine (10 Ϫ8 Ϫ10 Ϫ12 mol/L) increased EPC number and activity, whereas higher (toxic) concentrations (Ͼ10 Ϫ6 mol/L) were associated with cytotoxicity. In humans, Kondo et al demonstrated that chronic smokers (nϭ15) exhibit reduced EPC levels that can be restored after smoking cessation within 4 weeks.…”
Section: Smokingmentioning
confidence: 99%
“…59 Smoking has been identified as an important risk factor for reduced EPC numbers in one of the first studies on cardiovascular risk factors by Vasa et al 46 However, Wang et al recently demonstrated that the role of nicotine is more complex than initially expected. 60 In an experimental study, they demonstrated that low concentrations of nicotine (10 Ϫ8 Ϫ10 Ϫ12 mol/L) increased EPC number and activity, whereas higher (toxic) concentrations (Ͼ10 Ϫ6 mol/L) were associated with cytotoxicity. In humans, Kondo et al demonstrated that chronic smokers (nϭ15) exhibit reduced EPC levels that can be restored after smoking cessation within 4 weeks.…”
Section: Smokingmentioning
confidence: 99%
“…Chronic smok- ers have reduced EPC levels which can recover after smoking cessation within 4 weeks [28]. Wang et al recently demonstrated that nicotine may be a two-edged sword [29]. Low concentrations of nicotine increased EPC levels while higher concentrations (>10 -6 mol/L) were associated with decreased EPC levels.…”
Section: Cardiovascular Risk Factors Influence Epc Levels and Functionmentioning
confidence: 99%
“…However, Wang et al recently demonstrated that the r ole o f nicotine i s more complex than initially expected (94). In an experimental study, they demonstrated that low concentrations of nicotine (10-8-10-12 mol/L) increased EPC number and activity, whereas higher (toxic) concentrations (>10-6 mol/L) were associated with cytotoxicity.…”
Section: Cardiovascular Risk Factors and Epcsmentioning
confidence: 97%